The military instrument and its effectiveness in implementing foreign policy objectives: Experimenting with Ethiopia's and Kenya's 2011 operations in Somalia - Yigzaw, Tadie Degie; Mengisteab, Kidane (Ethiopian Journal of Social Sciences, 2023)
In the history of politics, states have viewed military intervention as one of their tools for foreign policy. However, many scholars do not agree on the effectiveness of military means in achieving the foreign policy objectives of states. Like other states, Ethiopia and Kenya have used the military as a means of foreign policy and tested their tools in Somalia practically. However, the effectiveness of their foreign policy tool has not been studied. That is why this article's main objective is to analyze the effectiveness of Ethiopian and Kenyan foreign policies that used military interventions to achieve their foreign policy goals in terms of outcomes. In doing so, the article employed a comparative case study methodology. Besides, the "good enough" approach is the proper theoretical lens that is used in this article to comprehend Ethiopia's and Kenya's operational outcomes. The analysis comes to the conclusion that both Kenya's and Ethiopia's military deployments in Somalia largely failed to accomplish their foreign policy goals. Accordingly, the findings reveal that using hard power as a tool of foreign policy without combining soft power is unsuccessful, as revealed by Ethiopia's and Kenya's military engagement in Somalia.